STUDENTS’ PERSPECTIVE TOWARDS ASYNCHRONOUS AND SYNCHRONOUS TEACHING AND LEARNING PROCESS IN A TOEIC PREPARATION CLASS - Dianita; Levita Dwinaya (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The globally spread Covid-19 pandemic has instantly changed the teaching and learningprocess. This study captures students’ perspective towards asynchronous and synchronous teachingand learning process in a TOEIC preparation program. The data gathered for the study were collectedthrough a questionnaire consisting of eight open ended questions, which were given to students of ahigher educational vocational institution in Bandung previously taking a one month TOEICpreparation program. The result indicates that students involved in this study prefer asynchronous elearningover synchronous because of the lack of infrastructure supports such as stable internetconnection and big internet quota. However, generally students have positive perspective towards theuse of both asynchronous and synchronous e-learning as those types of e-learning are proved to havegood impact on their learning.